How do different forms of early employment instability affect future employment chances? A factorial survey experiment with employers - Shi, LP (Emerald Publishing Limited, 2024)
Purpose Periodic economic instabilities and structural changes in the labour market have given rise to a variety of forms of job insecurity. This article compares the scarring effects of different forms of job insecurity on future employment chances, and how they vary across education groups. Design/methodology/approach Using a sample of real vacancies and data collected in a vignette experiment with employers in Switzerland, a country with a strongly developed vocational education and training (VET) system, this article investigates how employers evaluate a period of unemployment, job hopping and work experience in deskilling jobs when hiring candidates. Findings The findings reveal that work in deskilling jobs is by far more scarring than unemployment or job hopping. The study also demonstrates that applicants with upper secondary vocational education are impacted the greatest by all three forms of job insecurity. Originality/value The study makes use of real vacancies. While experiments have the strength of high internal validity, most experimental studies in recruitment research rely on students as respondents. As this study works with real employers hiring for positions it benefits from high external validity.